Pathophysiology and Clinical Applications of Gastro-Esophageal Reflux Disease - Kamran, Qindeel; Mund, Muhammad Danish; Ali, Hafiz Akbar; Barkat, Muhammad Qasim (Archives of Clinical and Biomedical Research, 2017)
Gastro-esophageal reflux disease is a persistent affliction of gastrointestinal tract upper part with the growing prevalence throughout the world. By the time there has been an increase in the cognizance of its pathophysiology, clinical presentation and management. The disease could be identified easily by the symptoms. Many of the risk components are involved in the occurrence of disease including medications, obesity, pregnancy and asthma. It can be diagnosed by a number of procedures like manometry, ambulatory pH monitoring , endoscopy and radiology. Although different drugs are being utilized to treat GERD but PPIs (Proton pump inhibitors) have shown remarkable achievement in the curing the disease. When proton pump inhibitors are utilized for the extended period several of the safety ways are being explored to avoid any side effect. There has been a debate over the use of long term medications and surgery for quite a long time. Although both surgery and long term usage of PPI’s have proven effective in managing the disease.